2014
DOI: 10.1007/s00330-014-3386-4
|View full text |Cite
|
Sign up to set email alerts
|

Logistic regression model for diagnosis of transition zone prostate cancer on multi-parametric MRI

Abstract: ObjectivesWe aimed to develop logistic regression (LR) models for classifying prostate cancer within the transition zone on multi-parametric magnetic resonance imaging (mp-MRI).MethodsOne hundred and fifty-five patients (training cohort, 70 patients; temporal validation cohort, 85 patients) underwent mp-MRI and transperineal-template-prostate-mapping (TPM) biopsy. Positive cores were classified by cancer definitions: (1) any-cancer; (2) definition-1 [≥Gleason 4 + 3 or ≥ 6 mm cancer core length (CCL)] [high ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
48
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 37 publications
5
48
0
Order By: Relevance
“…A different logistic regression model combining mean ADC value, normalised T2-weighted signal and maximum enhancement measured by dynamic contrast-enhanced (DCE) MRI was recently proposed to classify prostate cancer within the transition zone [13]. When detecting lesions with a Gleason score of 4 + 3 or greater and a diameter greater than 6 mm, the model led to an AUC of 0.71 (95 % CI 0.58-0.84) following leave-one-out regression analysis in 70 patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A different logistic regression model combining mean ADC value, normalised T2-weighted signal and maximum enhancement measured by dynamic contrast-enhanced (DCE) MRI was recently proposed to classify prostate cancer within the transition zone [13]. When detecting lesions with a Gleason score of 4 + 3 or greater and a diameter greater than 6 mm, the model led to an AUC of 0.71 (95 % CI 0.58-0.84) following leave-one-out regression analysis in 70 patients.…”
Section: Discussionmentioning
confidence: 99%
“…As a result of the considerable overlap in ADC values between high-and low-grade lesions, a recent study combined ADC values with parameters derived from other MRI sequences in a logistic regression model to detect cancers with a high Gleason score; the accuracy of the model was found to be similar to the accuracy of experienced radiologists [13]. Another study found that intravoxel incoherent motion (IVIM) parameters (the pure diffusion coefficient D t , the pseudo-diffusion fraction F p and the pseudo-diffusion coefficient D p ) derived from a biexponential fit to DW-MRI [14,15] correlate with the cancer's aggressiveness [16].…”
Section: Introductionmentioning
confidence: 85%
“…For the purpose of this study and to match with the target performance of mp-MRI as defined by recent consensus [24]; histopathologists identified all locations with clinically significant cancer based on volume assessment (0.2 ml) estimated by the cancer core length (CCL)>= 4 mm and/or the presence of Gleason pattern 4 disease [25]. Small volume (<0.2 ml) and low grade (<=Gleason 3+3) tumour was identified as clinically insignificant cancer.…”
Section: Prostate Populationmentioning
confidence: 99%
“…31,32 Logistic regression belongs to the class of generalized linear model based on the exponential distribution family. It is a statistical model that can describe the relationship between several predictor variables X 1 ; X 2 ; : : : ; X k and a dichotomous response variable Y (0 or 1).…”
Section: Logistic Model and Support Vector Machine Classifiersmentioning
confidence: 99%